2017
DOI: 10.3390/molecules22111866
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, and Antioxidant Activity of Polysaccharides Isolated from Cortex Periplocae

Abstract: In this study, crude Cortex Periplocae polysaccharides (CCPPs) were extracted with water. CCPPs were decolored with AB-8 resin and deproteinated using papain-Sevage methods. Then, they were further purified and separated through DEAE-52 anion exchange chromatography and Sephadex G-100 gel filtration chromatography, respectively. Three main fractions—CPP1, CPP2, and CPP3, (CPPs)—were obtained. The average molecular weights, monosaccharide analysis, surface morphology, and chemical compositions of the CPPs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In this context, some researchers have also reported that polymers with more rhamnose and mannose content are able to display better antioxidant activity (Wang et al, 2017). Thus, it could be assumed that the remarkable antioxidant effect of Rusenan was not due to a single element but the result of combination of many factors.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, some researchers have also reported that polymers with more rhamnose and mannose content are able to display better antioxidant activity (Wang et al, 2017). Thus, it could be assumed that the remarkable antioxidant effect of Rusenan was not due to a single element but the result of combination of many factors.…”
Section: Resultsmentioning
confidence: 99%
“…Production of GalactoPol and FucoPol isolated from Pseudomonas oleovorans and Enterobacter A47, respectively, are maximized under aerobic conditions, with carbon availability concomitant with nitrogen and oxygen limitation 38 . In contrast, gellan and cellulose production is favored in media supplemented with vitamins and amino acids [39][40][41][42][43][44] . We also investigated the optimal culture condition for DeinoPol production based on its sugar composition analyzed by Bio-LC mass spectrometry in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We used gradient ethanol precipitation to purify DeinoPol, but its high toxicity (LD 50 = 12.5 μg/mL) presents a limitation for its use as a cosmetic ingredient. We, therefore, used the Sevage method after ethanol precipitation to remove toxic, insoluble materials such as lipids and membrane proteins [41][42][43] . The final product was shown to be non-toxic at over 1000 μg/mL in NHEK-Ad (Supplement ary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations